SURVIVAL RATE DAN TOTAL AKUMULASI BIOMASSA PERMUKAAN DARI LIMA JENIS POHON YANG DIGUNAKAN DALAM EKSPERIMEN RESTORASI PADA LAHAN GAMBUT BEKAS TERBAKAR DI AREA TRANSISI CAGAR BIOSFER GIAM SIAK KECIL-BUKIT BATU DESA TANJUNG LEBAN, BENGKALIS, RIAU - Dian Indriani; Haris Gunawan; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Biosphere Giam Siak Kecil-Bukit Batu reserve was based on managed zonations as a multi-benefit management approach. This region has a fairly large carbon stocks stored in its natural peat swamp forest ecosystems. How ever the general condition of the peat swamp forest in the landscape Biosphere Giam Siak Kecil-Bukit Batu currently has suffered damage, especially in the buffer and transition zones. The threat to the existenceof protected areas are not only coming from forest fires factors alone, but also from encroachment and illegal logging. Therefore, is requires a recovery effort. This research aims to determine the survival rate and to estimate above ground biomass accumulation of the main tree species of peat swamp forest which was used to restore the burnt-peat. Estimate total biomass accumulation on the surface using allometric equations. Result of this research prove that the type of Jelutung (Dyera polyphylla) has the best survival rate among the values of other types (98%), while the species Pisang-pisang (Mezzettia parviflora) have a survival rate of 35%. Total above ground biomass accumulation on thehighest level found in Jelutung (Dyera polyphylla) it was 499.015 kg/ha/year, while the lowest total above ground biomass accumulation found in Meranti batu (Shorea uliginosa) 88.867 kg/ha/year.